UJI AKTIVITAS EKSTRAK KUNYIT (Curcuma domestica Val) TERHADAP LUKA INSISI PADA TIKUS PUTIH JANTAN GALUR WISTAR - , MARZAIN YUNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is rich in variety of biodiversity very numerous plants that can be processed as a medicine.The use of organic natural recources as an ingredient of a drug including part of the field of scope an alternative treatment and complementary namely traditional medicine.Hence with this research will learn about the mechanisms of healing of sores from a rhizome turmeric ( curcuma domestica val ). Matter used in this research is 75 tail of a mouse wistar that is divided into 5 group and each group of treatment there are 15 tail of a mouse who are subdivided into 5 a subgroup of time, collection of samples and each consisting of 3 tail of a mouse.To a group of -1 as control a solvent ( na-cmc 0.5 % ), a group of 2 as control madecassol Â® and three other groups as 3 variation a dose of an extract rhizomes turmeric ( 50, 100, and 200 g / 200 gbb ).Preparation given 1 time in four days in 1 day peroral.Adoption of a network of mice 12th, conducted on the clock 24, 48, 72, and 96 on meanwhile, measurement of the width of a wound done every day.The result of the measurement of the width of a wound, then calculated percentage closure of a wound.The network aims to observe the cells rankling in, fibroblast, hemoragi, and necrosis which are then analyzed by nested anova. From the research all variation doses extract rhizome of the turmeric having the effect of healing wound good than control diluent.Doses 200 Î¼g / 200 gbb can reduce an inflammatory reaction, in doses 100 Î¼g / 200 gbb can reduce the number hemoragi, while doses 50 Î¼ g / 200 gbb give a closure wound the fastest, increase the number of fibroblast, and capable of lowering number of cells necrosis.